Enantiomeric Recognition of α-Aminoacids by a Uranyl Salen-Bis-Porphyrin Complex - Gangemi, Chiara M. A.; Rimkaite, Ugne; Cipria, Federica; Trusso Sfrazzetto, Giuseppe; Pappalardo, Andrea (Frontiers in Chemistry, 2019)
A novel uranyl salen-bis-porphyrin complex, in which two porphyrin subunits and salen moiety were directly linked, was synthesised for the recognition of tetrabutylammonium (TBA) amino acids. This uranyl salen complex, due to the presence of porphyrins, represents the first example in which the luminescence properties are not quenched by the presence of the metal ion. UV/Vis measurements indicate the formation of 1:1 host–guest complexes, whereas fluorescence studies revealed that this complex acts as a receptor for the enantiomeric recognition of -aminoacids derivatives, with high association constants and an excellent enantiomeric discrimination between the two enantiomers of phenylalanine–TBA.